Open Science in Times of Coronavirus: Introducing the Concept of "Real-Time" Publication - Alexandre Hocquet (Substantia, 2020)
Who doesn't have an opinion about hydroxychloroquine? The recent developments of the latest research in Marseilles on the potential of this antimalarial drug to reduce the viral load of SARS-CoV-2 have been heating up. Obviously, the current pandemic is a sudden and unprecedented health crisis. Unexpectedness and scale are turning the outbreak into widespread panic: science is summoned to find solutions as soon as possible. In a sense, the worldwide situation is a way of asking how fast can science go. The famed publication from Didier Raoult's group 2 allows us to highlight an evolution in peer review practices, and this trend allows us to question what it means to be "open" in science.